Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1115/1.1345887
|View full text |Cite
|
Sign up to set email alerts
|

Spray Cooling Under Reduced Gravity Condition

Abstract: The present paper reports on the results of a series of authors’ parabolic flight experiments on spray cooling in addition to ground-based experiments in which the influence of heater orientation and the behavior of rebounded droplets were especially studied in detail. Water and FC-72 (perfluorocarbon) were employed alternatively as a test liquid sprayed from a single full-cone nozzle onto a Cr-plated surface of an electrically heated copper block for transient cooling experiments or onto a transparent ITO (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 15 publications
5
41
2
Order By: Relevance
“…For the unconfined spray, the vertical spray is slightly more efficient than the horizontal spray at a flow rate of 6.2 GPH. This is opposite to trends observed by Kato, et al (1994) and Yoshida, et al (2001). At 9.3 GPH, the opposite trend is observed for the unconfined flow.…”
Section: Experiments Without Electrical Forcescontrasting
confidence: 50%
See 1 more Smart Citation
“…For the unconfined spray, the vertical spray is slightly more efficient than the horizontal spray at a flow rate of 6.2 GPH. This is opposite to trends observed by Kato, et al (1994) and Yoshida, et al (2001). At 9.3 GPH, the opposite trend is observed for the unconfined flow.…”
Section: Experiments Without Electrical Forcescontrasting
confidence: 50%
“…Yoshida, et al (2001) found that spray cooling in the nucleate boiling regime was more effective in simulated microgravity (jig) than in terrestrial gravity when water was used, but when the commercial coolant FC-72 was used, only a slight improvement was seen. Yoshida et al simulated jig conditions by rotating their apparatus 180 degrees, changing the direction of the heated surface from upward facing to downward facing.…”
Section: )mentioning
confidence: 99%
“…Several microgravity spray cooling experiments were performed by Yoshida 6 and Kato 7 . The experiments looked at both transient and steady state spray cooling in microgravity during reduced gravity aircraft flights.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%
“…To be effective, these proposed thermal management approaches must operate in extreme space environments. Several thermal management approaches have been or are being considered for space environments such as jet impingement 1 , two phase flow and heat transfer 2 , pool boiling 3,4,5 , and spray cooling 6 . An analytical and experimental study performed by Labus 1 determined the free surface shape of a jet impinging on an unheated flat disk in microgravity, Fig.1.…”
Section: Introductionmentioning
confidence: 99%
“…Sone et al [9] and Yoshida et al [10] showed that during microgravity (using FC-72), the critical heat flux (CHF) increased by 14% at the center of the heater. Their studies also showed a decrease in heat transfer along the peripheral due to the reduction in gravity.…”
Section: Expected Resultsmentioning
confidence: 99%